(Un)Certainty in the News: Journalists' Decisions on Communicating the Scientific Evidence of Nanotechnology. (March 2015) - Guenther, Lars; Froehlich, Klara; Ruhrmann, Georg
Science journalists are responsible for the media content about nanoscale science and technology, and its representation as scientifically certain or uncertain. This article applies the reasoned action approach (RAA) to identify factors having an impact on journalists' decisions on how to depict aspects of scientific evidence (= scientific (un)certainty). Results of interviews with science journalists ( n = 21) from diverse media channels showed that they adopt different coverage styles when representing (un)certainty. To find reasons for that, behavioral, normative, and control beliefs were investigated, and a model of science journalistic depiction behavior with respect to scientific evidence was constructed.